Adopting Intelligent Tutors in the Use of Digital Marketing Applications: A Case Study of MSMEs in Curug Sangereng Village, Banten - Santo Fernandi Wijaya; Eric William; Wiratama, Jansen (JUAN (Jurnal Ultima Abdimas Nusantara), 2025)
Technological digitalization has had a significant impact on Micro, Small, and Medium Enterprises (MSMEs), enhancing their operations and marketing capabilities. This progress is largely driven by the optimal utilization of information systems. However, many MSMEs still underutilize these systems, leading to inefficiencies in their operations. While previous studies have examined critical factors in achieving MSME digitalization, further research is needed from alternative perspectives to explore solutions to the complex challenges MSMEs face in the digital transition. This study employs a literature review method to map key factors from the perspectives of People, Process, and Technology. Data was then collected through a survey and analyzed using the SmartPLS method to determine the ranking of primary indicators, which serve as a foundation for designing a digital marketing model and application. The findings indicate that training and education are significant indicators that can assist MSMEs in adopting intelligent tutors to practically utilize digital marketing applications according to their specific business needs. The outcome of this research is a digital marketing model designed to help MSMEs contribute to achieving SDG 9 (Industry, Innovation, and Infrastructure), by evaluating the model to identify best practices in business transaction management and enhancing MSME performance.